Tingkat Kesadaran Lingkungan Mahasiswa sebagai Kontribusi terhadap Tujuan Pembangunan Berkelanjutan (SDGs) - Edwin, Tivany; Khairul, Ujang; Nur, Ansiha; Mardatillah, Regina; Arif Satria, Muhammad (Dampak, 2025)
University students are key agents in promoting environmental sustainability, making it essential to assess their level of knowledge, attitudes, and actions regarding environmental awareness. This study aims to evaluate environmental awareness among university students through a structured questionnaire survey. The instrument was distributed to 71 students across different academic levels at a university in West Sumatra Province. The results indicate that while most students possess a basic understanding of environmental issues, their ability to analyze, synthesize, and evaluate such issues remains limited. In terms of attitudes, students generally demonstrate positive dispositions, although further development is needed to foster active participation and social responsibility. Regarding environmentally conscious actions, students have not yet consistently adopted sustainable behaviors, particularly at the level of habitual and innovative practices. Key behaviors that require improvement include waste separation, refusal to use plastic bags, the use of reusable food containers, and recycling practices. These findings highlight the need for more practical and reflective environmental education at the higher education level. Keyword: university students, knowledge, attitude, action, environment